Addressing Women and Minorities on Social Media by the 2016 U.S. Presidential Candidates. (August 2019) - Bailey, Mandi Bates; Nawara, Steven P.
Donald Trump's bombastic statements regarding women and minorities were a constant theme in the 2016 presidential election and attracted attention from both the mainstream media and his opponent, Hillary Clinton. Given the increasing use of social networking sites among political actors and the public, as well as the focus given to women and minorities in the 2016 election, we utilize a content analysis of presidential candidates' social media activity in the months preceding the election in order to better understand how the candidates addressed women and minorities. We ultimately find that Democratic candidate Hillary Clinton out-posted Trump in both positive and negative content in the categories of women's issues; lesbian, gay, bisexual, and transgender issues; race; and immigration. However, this is not the case with issues involving crime and police, which was a lens through which Trump was more likely to approach race-related issues. In many instances, the candidates also appeared to strategically target content-specific posts to the social media platforms where they would be most likely to be seen by women or the minority group most closely related to the post's content.